Soundbites: Groups, Bands & Orchestras - THOMAS, ROGER (Capstone Global Library Ltd Oxford, United Kingdom, 2002)
Soundbites has been produced to help children develop a greater understanding of the orchestra and its sections, instruments and the sounds made by the instruments. The series also provides information on how these instruments and sounds are used outside the orchestral context. Each book explains: - the place of the instruments within the orchestra - how the sounds are produced - how the instruments work and the sounds they make - the history and development of the instruments